Chemosensory perception and food preferences in colorectal cancer patients undergoing adjuvant chemotherapy. (December 2020) - Postma, E.M.; Kok, D.E.; de Graaf, C.; Kampman, E.; Boesveldt, S.
Summary: Background and aim: Cancer is one of the major public health problems, with colorectal cancer being one of the most occurring types of cancer. During treatment, patients may experience changes in their dietary intake due to side-effects of treatment, like changes in chemosensory perception, i.e. smell and taste function. This study investigated alterations in chemosensory perception and food preferences in colorectal cancer patients during and after adjuvant chemotherapy. Methods: Objective olfactory and gustatory function were measured by the Sniffin' Sticks and the Taste Strips test. Subjective smell and taste perception were determined with a questionnaire, while food preferences were assessed with a computer-based ranking task. To investigate changes during chemotherapy, patients undergoing adjuvant chemotherapy were measured before the start, halfway through (approximately 3 months after the start of adjuvant chemotherapy), and within one month after finishing chemotherapy (longitudinal measurements, n = 15 patients). As a comparison group, colorectal cancer patients not undergoing chemotherapy (n = 20), underwent the same measurements at similar time points. To measure changes after treatment, chemosensory perception and food preferences of patients who had undergone chemotherapy treatment were measured once, either at 6, 12 or 24 months after diagnosis (cross-sectional measurements; n = 20 for all time points). Changes during treatment were assessed using linear mixed model analyses, and changes after treatment were assessed with a one-way ANOVA or a Kruskal Wallis test. Results: Objective olfactory and gustatory function did not differ statistically significantly between any of the groups and at any time point during or after treatment (all p > 0.05). In contrast, subjective smell (F(1, 84) = 8.17, p = 0.005) and taste (F(1, 99) = 4.08, p = 0.046) perception were rated statistically significantly lower by patients undergoing chemotherapy than the comparison group during treatment. At 6 months after diagnosis, patients who underwent chemotherapy rated their subjective taste perception significantly lower than patients at 12 and 24 months after treatment (F(2, 57) = 12.05, p = 0.002). Food preferences did not change during treatment, or thereafter (all p > 0.05). Preference for protein-rich foods was positively correlated with objective gustatory function (r = 0.36, p < 0.001), while the preference for low-energy foods showed a negative correlation with objective gustatory function (r = −0.28, p = 0.004). Conclusions: Similar to other cancer patient populations, mainly subjective smell and taste perception are affected in colorectal cancer patients undergoing adjuvant chemotherapy. Changes in objective olfactory and gustatory function in relation to chemotherapy were not detected by the tests used in our study nor did food preferences change. However, it should be noted that subjective changes in smell and taste perception can affect subsequent flavor perception and food enjoyment, which might negatively impact eating behavior and nutritional intake.